2 year followup of patients with diabetes mellitus nephropathy showing albuminuria reversal following angiotensin converting enzyme inhibitors - Gopinath, S. (Medknow Publications & Media Pvt Ltd, 2012)
INTRODUCTION: Two-year follow-up of patients with diabetes mellitus (DM) nephropathy shows albuminuria reversal following angiotensin converting enzyme (ACE) inhibitors. AIM: To study about a clinical profile of 2-year follow-up of patients with DM nephropathy showing albuminuria reversal following ACE inhibitors. MATERIALS AND METHODS: Twenty patients were taken up for study with duly informed consent and suggested for glycemic profile with HbA1C. Baseline renal function, urine microscopy, albuminuria, and other microvascular complications such as neuropathy and retinopathy. These patients were followed up for a period of 2 years with every month follow-up and monthly dose titration of ACE inhibitors, enalapril (Quote: Dr. M. K. Mani), to a maximum tolerable dose and checked after 1 week for raise in creatinine and potassium. INCLUSION CRITERIA: Twenty patients, who have attended a secondary level diabetic clinic with diabetic nephropathy and are on regular follow-up for 2 years, were selected. EXCLUSION CRITERIA: Sick patients requiring parenteral feeds, IV antibiotics, co-morbid conditions such as autonomic gastroparesis and diabetic foot infections, type 1 diabetes and other known kidney disease, chronic kidney disease on dialysis are excluded from the study. EXPECTED RESULT: Reversal of albuminuria. CONCLUSION: Enalapril is a safe, cheaper ACE inhibitors and the good dose titration coupled with early screening for DM nephropathy really help in halting the progression of chronic kidney disease from DM nephropathy.